Enteroadsorbent Polymethylsiloxane Polyhydrate vs. Probiotic Lactobacillus reuteri DSM 17938 in the Treatment of Rotaviral Gastroenteritis in Infants and Toddlers, a Randomized Controlled Trial - Markovinović, Leo; Knezović, Ivica; Kniewald, Tihana; Stemberger Marić, Lorna; Trkulja, Vladimir; Tešović, Goran (Frontiers in Pediatrics, 2020)
Purpose: We aimed to compare two adjunct therapies for the treatment of childhood rotavirus gastroenteritis (RVGE). We took standard treatment, probiotic Lactobacillus reuteri (BioGaia®), vs. novel treatment, enteroadsorbent polymethylsyloxane-polyhydrate (PMSPH) i.e. Enterosgel®. Methods: A randomized, open-labelled, clinical controlled trial took place in University Hospital for Infectious Diseases (UHID) at Zagreb, Croatia. Participants were one hundred and thirty children aged 6-36 month without significant chronic comorbidity having acute rotaviral gastroenteritis for less than 48 h of symptom duration. One group of participants (N=65) were given standard therapy with L. reuteri for five days while the other group was treated with the same duration of PMSPH therapy. The efficacy of investigated therapies was tested on three levels - duration of symptoms, duration of hospital stay and the total number of liquid stools. Duration of symptoms and hospital stay length were analyzed by proportional hazard regression. The total number of liquid stools was analyzed using the Mann-Whitney test. Results: There was no difference in the treatment efficacy between the two regimens. Also, no significant side effect was observed in both groups. Conclusion: Novel enteroadsorbent polymethylsyloxane polyhydrate has the same efficacy as probiotic L. reuteri in the treatment of rotaviral gastroenteritis in preschool children.